THERAPEUTIC EFFICACY OF MIFEPRISTONE, CABERGOLINE AND CLOPROSTENOL FOR TERMINATION OF PREGNANCY IN BITCHES - REDDY, K RAM CHANDRA; RA0, K SADA SIVA; SOLOMON RAJU, K G; RAGHAVENDER, K B P; REDDY, A GOPAL (The Indian Journal of Animal Reproduction, 2023)
A total of 24 cases of misalliance in bitches were utilized to study the efficacy of various therapeutic protocolsfor termination of pregnancy after early confirmation of pregnancy. These bitches were randomly allotted to threetreatment and one control group with 6 bitches in each group. Pregnancy was terminated 100 per cent in all thethree treatment groups. The incidence of abortion and resorption in -mifepristone treated group was 15.38 and84.62, in cabergoline plus cloprostenol group was O and 100, in cloprostenol group was 26.09 and 73.91 and incontrol group was O and 6.66 per cent respectively. Treatment groups had significantly shorter inter estrous cycleinterval than control group. The average number of pups born in the next whelping was 3. 5 ± 0.22, 5.67 ± 0 .33, 3.34± 0.55 and 5.0 ± 0.58 in mifepristone, cabergoline plus cloprostenol, cloprostenol and control groups respectively.These three treatment protocols can be effectively used for the termination of pregnancy in bitches.
Keywords: Bitches; Misalliance; Mifepristone; Cabergoline; Cloprostenol